Field demonstration of continuous monitoring of a steel railway bridge - Deepthi, T.M.; Saravanan, U.; Prasad, A. Meher (Journal of Structural Engineering, 2024)
Many railway bridges in India are aged requiring an analysis on their current health. Appropriate instrumentationis necessary to determine the health of the bridges. This paper explains the instrumentation philosophy followed andits implementation in the field for continuous monitoring of a railway bridge. The bridge considered for this studyis a single span steel plate girder bridge. Using a wired data acquisition system the bridge was monitored for 125days. Also, an economical wireless data acquisition system developed in-house was validated using this wired dataacquisition system. Finally, the collected strain time histories are summarized in the form of count versus strain range,as determined from the rainflow count algorithm. Thus, a viable methodology for continuous monitoring of railwaybridges is demonstrated which may be used to assess the health of the bridge and arrive at rational design loads forrailway bridges.